+Brettanomyces bruxellensis Displays Variable Susceptibility to Chitosan Treatment in Wine - Paulin, Margot; Miot-Sertier, Cécile; Dutilh, Lucie; Brasselet, Clément; Delattre, Cédric; Pierre, Guillaume; Dubessay, Pascal; Michaud, Philippe; Doco, Thierry; Ballestra, Patricia; Albertin, Warren; Masneuf-Pomarède, Isabelle; et al. (Frontiers in Microbiology, 2020)
Brettanomyces bruxellensis is the main spoilage microbial agent in red wines. The use of fungal chitosan has been authorized since 2009 as a curative treatment to eliminate this yeast in conventional wines and in 2018 in organic wines. As this species is known to exhibit great genetic and phenotypic diversity, we examined whether all the strains responded the same way to chitosan treatment. A collection of 53 strains of B. bruxellensis was used. In the conditions of the reference test, all were at least temporarily affected by the addition of chitosan to wine, with significant decrease of cultivable population. Some (41%) were very sensitive and no cultivable yeast was detected in wine or lees after 3 days of treatment, while others (13%) were tolerant and, after a slight drop in cultivability, resumed growth between 3 and 10 days and remained able to produce spoilage compounds. There were also many strains with intermediate behavior. The strain behavior was only partially linked to the strain genetic group. This behavior was little modulated by the physiological state of the strain or the dose of chitosan used (within the limits of the authorized doses). On the other hand, for a given strain, the sensitivity to chitosan treatment was modulated by the chitosan used and by the properties of the wine in which the treatment was carried out.